The Application Of Audiovisual Media On The Learning Motivation Of Students With Special Needs - Kartika, Neng; Surya, Havid; Sari, Novita; Umalihayati; Sari, Muthia (PIAUD Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah, 2025)
The low learning motivation of students with special needs (PDK) in Serang City is evident from their lack of focus, participation, and active involvement during learning. This condition shows that conventional learning methods have not been able to accommodate the individual needs and learning styles of each child. This study aims to analyse the application of audio-visual media in increasing the learning motivation of PDK. Using a descriptive qualitative approach, the participants consisted of three PDK children with different characteristics, while the data was obtained through observation, interviews, and documentation, then analysed through data reduction and conclusion drawing. The results showed that audio-visual media was effective in increasing learning motivation, as indicated by increased enthusiasm, curiosity, perseverance, and participation among children. The media was adjusted according to the children's needs, such as large text for the deaf, simple animations for children with autism, and interactive displays for children with concentration disorders. This study provides hope for the development of inclusive learning media and encourages collaboration between teachers and parents in supporting PDK learning motivation in a sustainable manner.